Bilateral trade with loss-averse agents - Jean-Michel Benkert (University of Zurich, Department of Economics, 2022)
The endowment and attachment effect are empirically well-documented in bilateral trade situations. Yet, the theoretical literature has so far failed to formally identify these effects. We fill this gap by introducing expectations-based loss aversion, which can explain both effects, into the classical setting by Myerson and Satterthwaite (1983). This allows us to formally identify the endowment and attachment effect and study their impact on information rents, allowing us to show that, in contrast to other behavioral approaches to the bilateral trade problem, the impossibility of inducing materially efficient trade persists in the presence of loss aversion. We then turn to the design of optimal mechanisms and consider the problem of maximizing the designer's revenue as well as gains from trade. We find that the designer optimally provides the agents with full insurance in the money dimension and, depending on the distribution of types, optimally increases or decreases the trade frequency in the presence of loss aversion.
Keywords: C78; D01; D02; D82; D84; D90; 330; bilateral trade; loss aversion; mechanism design; endowment and attachment effect; Mechanismus-Design-Theorie; Rent Seeking; Verlustaversion; Bilateraler Handel; Mechanismus-Design-Theorie; Rent Seeking; Verlustaversion; Bilateraler Handel